2000
DOI: 10.1038/sj.bdj.4800393
|View full text |Cite
|
Sign up to set email alerts
|

Dental care for the patient with a cleft lip and palate. Part 1: From birth to the mixed dentition stage

Abstract: This is the first of two articles looking at dental care for the patient with a cleft lip and palate. Part 1 looks at the needs of the child with a cleft lip and palate from birth through to the mixed dentition stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
8
0
5
Order By: Relevance
“…We see the predisposing factors mentioned in the literature (Paul and Brandt, 1998; Rivkin et al, 2000; Cheng et al, 2007) as main causes of the higher prevalence of caries in patients with severe cleft forms. Hence, a preoperatively inserted drinking plate can lead to an early colonization of the oral cavity with Streptococcus mutans bacteria and lactobacilli (Bokhout et al, 1996; van Loveren et al, 1998).…”
Section: Discussionmentioning
confidence: 85%
“…We see the predisposing factors mentioned in the literature (Paul and Brandt, 1998; Rivkin et al, 2000; Cheng et al, 2007) as main causes of the higher prevalence of caries in patients with severe cleft forms. Hence, a preoperatively inserted drinking plate can lead to an early colonization of the oral cavity with Streptococcus mutans bacteria and lactobacilli (Bokhout et al, 1996; van Loveren et al, 1998).…”
Section: Discussionmentioning
confidence: 85%
“…Poor oral health may interfere with healing following a surgical intervention, such as alveolar bone graft [14, 15], or significant dental decay may preclude important orthodontic treatment [16]. Furthermore, early loss of teeth may complicate the orthodontic treatment provided for children with CLP [17]. …”
Section: Methodsmentioning
confidence: 99%
“…1 Associated dental defects can include: incisor displacement, presence of supernumerary teeth, hypodontia, enamel hypoplasia, microdontia and unusual shaped teeth, transposition and geminated/fused teeth. 2 Evidence has shown that this group of patients are at a higher risk of developing dental caries compared with the general population 3 ( Fig. 1).…”
Section: Introductionmentioning
confidence: 92%